2001
DOI: 10.1007/pl00012014
|View full text |Cite
|
Sign up to set email alerts
|

A review of the ecological parameters and implications of subsociality in Parastrachia japonensis (Hemiptera: Cydnidae), a semelparous species that specializes on a poor resource

Abstract: Subsocial behavior or postovipositional parental care in insects has evolved in response to a variety of environmental stresses and ranges from briefly guarding eggs after oviposition to elaborate nidification and provisioning behaviors. Investment in parental care bears various costs, and should not continue beyond the point at which the costs to future reproductive success exceed the benefits to current reproductive effort. Progressive provisioning is a rare form of subsociality in insects. Females of the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 26 publications
3
36
0
Order By: Relevance
“…However, the mechanism for vertical transmission of the symbiont in P. japonensis is not known and should be studied. Because of the peculiar ecology and behavior of this insect (7,41), we suggest several possible mechanisms for vertical transmission of the symbiont. The symbiont may be transmitted by contamination of the egg surface with maternal symbiont-containing excrement upon oviposition, as reported for the Pentatomidae, Acanthosomatidae, Scutelleridae, and Pyrrhocoridae (1,18,19,23,30,31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism for vertical transmission of the symbiont in P. japonensis is not known and should be studied. Because of the peculiar ecology and behavior of this insect (7,41), we suggest several possible mechanisms for vertical transmission of the symbiont. The symbiont may be transmitted by contamination of the egg surface with maternal symbiont-containing excrement upon oviposition, as reported for the Pentatomidae, Acanthosomatidae, Scutelleridae, and Pyrrhocoridae (1,18,19,23,30,31).…”
Section: Resultsmentioning
confidence: 99%
“…P. japonensis (Fig. 1A) is known for its peculiar ecology and behavior, including a prolonged prereproductive nonfeeding period for newly emerged adults that lasts for 9 months, maternal care of eggs in an underground nest, and maternal collection and provisioning of food (fruits) for nymphs (7,41,43). A previous study reported that when adult insects were treated with an antibiotic in the nonfeeding period, the uricase activity in the midgut was significantly reduced and the mortality of the insects increased dramatically (20).…”
mentioning
confidence: 99%
“…dioecious) species endemic to Japan, forms a specialized phoretic association with its dispersal host, the shield bug Parastrachia japonensis, such that the nematode life cycle synchronizes with that of the insect [39]. The shield bug is also a specialist species, feeding only on the fruits of the tree Schoepfia jasminodora, and having synchronized its own life cycle such that its reproductive period matches fruit availability [40]. The natural history of C. japonica is probably the best understood for any species of Caenorhabditis (figure 1a and Material and methods), and thus provides a unique opportunity to investigate patterns of genetic variation in relation to its ecology and specialized association with its host.…”
Section: Introductionmentioning
confidence: 99%
“…The bugs with extended parental behavior are: Sehirus cinctus cinctus (Palisot de Beauvois) (Sites & McPherson 1982;Agrawal et al 2004Agrawal et al , 2005; Adomerus triguttulus (Motchulsky) (Kudo & Nakahira 2004Kudo et al 2006;Nakahira & Kudo 2008); Adomerus variegatus (Signoret) (Mukai et al 2010); Canthophorus niveimarginatus Scott (Sehirinae) (Filippi et al 2009;Baba et al 2011); and the most studied Parastrachia japonensis Scott (Parastrachidae) (Tachikawa & Schaefer 1985;Tsukamoto & Tojo 1992;Tsukamoto et al 1994;Filippi et al 1995aFilippi et al , 1995bFilippi et al , 2000aFilippi et al , 2000bFilippi et al , 2001Filippi et al , 2002Filippi et al , 2005Nomakuchi et al 1998;Hironaka et al 2005Hironaka et al , 2007aHironaka et al , 2007bHironaka et al , 2007cTojo et al 2005). In a laboratory experiment adults and nymphs of Adrisa magna Uhler were observed to carry seeds of Sophora japonica L. (Leguminosae) to shelter places allowing communal feeding and possible provisioning for nymphs (Takeuchi & Tamura 2000).…”
Section: Introductionmentioning
confidence: 99%